A connecticut yankee in king arthur's court eaudiobook - Mark Twain (Recorded Books Inc., 1988)
When Hank Morgan is cracked on the head by a crowbar in 19th-century Connecticut, one of literature's most extraordinary fantasy tales begins to unfold. Humorous, devilishly insightful, and resoundingly contemporary, A Connecticut Yankee in King Arthur's Court remains one of the most celebrated stories in the canon of American writing. Awakening to find himself in the England of King Arthur, Morgan discovers a world of fear, injustice, and ignorance hiding behind a Utopian mirage. The tough-minded Yankee-the embodiment of scientific knowledge-must overcome daunting obstacles, including Merlin the Magician, as he sets out to enlighten sixth-century England. Only Mark Twain's unparalleled gift for story-telling could produce this acrobatic tour de force that moves from broad comedy to biting social satire, and from the pure joy of wild high jinks to deeply probing insights into the nature of man. Norman Dietz's wry narration and wonderful comedic sense will enchant listeners for generations to come.